Internal marketing and the commitment of the workers of the multiple services cooperative el Tumi – Trujillo 2021 - Pando Ezcurra , Ivy Samanta (2023)
The The investigation that has been carried out is a basic study, whose main objective has been to determine the existing relationship between internal marketing and the organizational commitment of the workers of the Cooperativa de Servicios Múltiples el TUMI Sucursal Trujillo.This is a study with a descriptive, correlational, quantitative, non-experimental and cross-sectional scope. To collect data, two instruments were developed: a structured questionnaire that measures the internal marketing variable, and the checklist that examines the organizational commitment variable. Both were applied to a sample made up of 80 workers from the TUMI Multiple Services Cooperative This instrument was subjected to a validation and reliability process, which was carried out by experts in the specialty. After reviewing the tests applied and submitting the data to analysis, the results obtained made it possible to show that there is a significant link between internal marketing and the organizational commitment in the Cooperativa de Servicios Múltiples el TUMI - Trujillo 2021, so if strategies are proposed to improve internal marketing in workers, this will make them get involved and identify with the institution, achieving a high organizational Each commitment.